Is transition between subtypes of pemphigus possible? A series of pemphigus vulgaris patients showing the transition to pemphigus foliaceus - Rifkiye Kucukoglu; Tugba Atci; Gizem Pinar Sun (Sociedade Brasileira de Dermatologia, 2023)
Abstract Background Pemphigus vulgaris (PV) and pemphigus foliaceus (PF) are subtypes of pemphigus with distinct clinical and laboratory features. The transition between these two subtypes has rarely been reported previously. Methods The data of PV patients who exhibited clinical and immunoserological transition to PF during the follow-up period were retrospectively evaluated regarding their demographical, clinical, and laboratory characteristics. Results Among 453 patients diagnosed with PV, 13 (2.9%) patients exhibited clinical and immunoserological transition from PV to PF. The mean age of PV patients at the time of diagnosis was 39.8 ± 14.7 (19‒62) years and 7 (53.8%) of them were female. These patients showed clinical and immunoserological transition from PV to PF after a period ranging from 4 months to 13 years (mean 36.2 ± 41 months). In addition to typical clinical features of PF, all patients had positive anti-desmoglein-1 and negative anti-desmoglein-3 antibody levels after the clinical transition had occurred without any mucosal involvement. During a mean 7.8 ± 5.8 (2‒21) years of follow-up period after the transition from PV to PF, only one female patient had experienced a re-transition to PV characterized by a relapse of disease involving mucosal surfaces with positive anti-desmoglein-3 antibody levels following a 5-year period of remission period without treatment. Study limitations Single-center study with a retrospective study design. Conclusion Our series is the largest group of patients reported to show the transition from PV to PF to date with a long follow-up period. The reason behind the disappearance of anti-desmoglein-3 antibodies and the pathogenesis of this phenomenon is not yet elucidated.